The Impact Of Service Quality Towards Customer’s Loyalty At Pt. Odiseus International Medan - Edward Harnjo; Sri Aprianti Tarigan; Susanto; Benny Lim; Eddy (Universitas Muhammadiyah Palu, 2026)
Globalization also has motivated managers to develop products or services quality that the company can compete in the world. Besides that, the managers of the company engaged in services sector need to carefully consider all situation and the conditions in order to providing the best service. Business opportunities in the services sector cannot be separated from the dynamics of the situation and external factors. In order to survive and make a profit that is planned, company is required to adapt products and services to the customer’s needs. Service companies should provide better service to its customers. The purposes of this research are to know the influence of service quality towards customer loyalty at PT Grand Odiseus International Medan. This research is done by using descriptive research and correlational design. Research methods which used are descriptive statistic analysis, validity and reliability test, simple linear regression, coefficient correlation, coefficient of determinant and Z testing. The result of this research is that there is influence of service quality towards customer loyalty in PT Grand Odiseus International Medan. In Z test, it can be determined that Zcount > Ztable (7.519 > 1.96). Therefore, hypothesis alternative is accepted that there is influence of service quality toward customer loyalty at PT Grand Odiseus International Medan. In correlation test, it can be know that service quality as independent variable (X) has strong positive relationship with customer loyalty in PT Grand Odiseus International Medan. In determinant test, it can be known that customer loyalty can be explained in 61.5% by service quality variable in PT Grand Odiseus International Medan while the rest as 38.5% can be explained by other variables which is not studied in this research. In linear regression analysis, it can be determined linear regression equation in Y = 0.111 + 0.619X. The regression coefficient is 0.619 that means increasing 1 unit of service quality variable can increase customer loyalty in 0.619 unit.